Die Christologiese en Pneumatologiese grondslag van die homiletiek: Perspektiewe vanuit A. A. van Ruler se denke - Vos, Casparus Johannes Adam (Verbum et ecclesia, 1993)
The ChristologicaI and Pneumatological basis of homiletics Perspectives from A. A. van Ruler’s reflections A. A. van Ruler’s thorough thinking about the differences between the Christological and Pneumatological structures indicates a way for homiletics. In this article the homiletic perspectives which arise from Van Ruler’s reflections are exploited.